Factors Influencing the Adaptation Behaviour of Rice Growers to Climate Change in Andhra Pradesh, India (Indian Journal of Extension Education, 2025)
The rice producers of Andhra Pradesh face the problem of declining productivity due to climate change factors. Climate change has hit the paddy growers of Andhra Pradesh hard and they need to adopt adaptation practices to counter the effects of changing climate. The study has identified and ranked the adaptation techniques followed by 240 paddy growers on the basis of extent of adoption. Multiple regression analysis was done to identify the factors influencing climate change adaptation behaviour of the rice cultivators. It was observed that education, farm income and information seeking behaviour have a positive effect on the adaptation behaviour, whereas farm size, farmer to farmer information exchange and change resistance were found to influence negatively the adaptive behaviour of farmers to climate change. The problems faced by the farmers in adaptation to climate change have also been identified and ranked. Lack of suitable varieties and quality seeds, price fluctuation in the market, low technical knowledge on climate resilient rice cultivation and lack of weather based insurance for rice cultivation were the most important problems that the rice cultivators faced in adaptation to climate change.